Managing Flood Water of Hill Torrents as Potential Source for Irrigation - Wan Faizal, Wan Ishak; Nasly, M. A.; Saher, F. N.; T. A. A., Kadir; N. K. E. M., Yahaya (Wiley, 2013)
This paper presents an integrated methodology for sustainable development planning to conserve the excess water resources. This developed methodology takes advantage of geographic information systems software to integrate its strength to manage the flood impacts. This approach is of dual purpose: first, to reduce the flash flood hazard of hill torrents; and second, to make use of flood water as a source of irrigation by conserving flood water in an earthen reservoir. The developed integrated methodology works as a decision-making system for selection of best site selection for earthen reservoir. The results for three potential sites for earthen reservoir supports in a decision-making process for best site for reservoir by analysing calculations for storage capacity, earthen works, and lengths of canals from reservoirs to agricultural land. This study investigated that the tools of geoinformatics have the potential to resolve the engineering challenges linked with mitigation of flood hazards. It is evident from the study that practical considerations for future turn the study into an informational tool to mitigate flood.